O efeito da autoeficácia no comportamento ético em negociações - Moura Neto, José Andrade (2017)
Purpose – The purpose of this work is to evaluate the influence of self-efficacy in negotiation on ethical behavior. Additionally, this research aims to identify a mediator that justifies this effect. Design/Methodology - The research was divided into two independent experiments. Initially, self-efficacy in negotiation was manipulated, being half in high and half in low self-efficacy. After that, in these two groups, ethically questionable behavior was measured in a virtual interactive negotiation. The second study had a 2x2 experimental design. Firstly, self-efficacy was manipulated. Subsequently, moral disengagement was manipulated. So, as in the first study, ethically questionable behavior was measured in an interactive negotiation. Findings – We have shown that self-efficacy is negatively related to ethically questionable behavior in negotiations. In addition, we have identified that ethically questionable behavior in a negotiation is mediated by moral disengagement. Research limitations - The main limitation of this research is that it is based on a virtual negotiation. In addition, it is a distributive negotiation or bargain. Future research can evaluate these results in a context of real interaction between individuals and in integrative negotiations. Practical implications - From these results, organizations can identify a potential cause of ethically questionable behavior. Thus, acting in the self-efficacy of their representatives in negotiations can deactivate mechanisms involved in the moral disengagement of those with low levels of self-efficacy. Social implications - By identifying sources of unethical behavior, organizations can avoid dishonest behavior among their employees and contribute to more ethical negotiations in the society. Additionally, they can reduce the probability of corporate and social ethical scandals and, for instance, reduce the damage to their company. Originality - To our knowledge, this is the first study that relates self-efficacy in negotiations and ethics.